The Virtues of Omnisubjectivity - Taliaferro, Charles (Roczniki Filozoficzne, 2025)
After observing the concord between Zagzebski’s philosophy of God and my own, questions are raised about her use of the term “objectivity,” her depiction of the history of subjectivity, and other matters. Zagzebski’s work is commended as an important contribution to philosophical reflection on divine attributes, religious practice, and inter-religious dialogue.